The Relationship between Stress and Loneliness with Depression in the Elderly People - Ni Ketut Ari Cendani; Putu Ayu Emmy Savitri Karin; Ni Made Dian Sulistiowati; Kadek Eka Swedarma (Babali Publisher, 2023)
Introduction: Depression is a condition that can cause elderly people to experience mental or emotional disorders due to stress and loneliness. Stress is something that can disturb the elderly caused by anxiety and loneliness due to changes in roles in the family or in their lives. The purpose of this study was to determine the relationship between stress and loneliness with depression in elderly people in Banjar Kawan, Tampaksiring, Bali. Methods: This study used a cross-sectional design with 68 elderlies recruited as respondents based on inclusion criteria by using purposive sampling techniques. The instruments used included the Perceived Stress Scale (PSS-10), UCLA Loneliness Scale Version 3, and Geriatric Depression Scale (GDS). The results of this study showed that most of the respondents aged 64 years, female, last education was elementary school, marital status was married with an income of < IDR 500,000. Results: The correlation results showed a significantly weak positive correlation between stress and depression (r = 0.284, p = 0.019) and loneliness with depression (r = 0.254, p = 0.037). The results of multiple linear regression showed that stress (β = 0.266) has the most effect on the occurrence of depression compared to loneliness (β = 0.039) so the higher the stress felt, the higher the symptoms of depression in the elderly. Conclusion: It is hoped that the elderly could improve their health by actively participating in many activities in order to prevent the symptoms of depression from getting worse.